2021
DOI: 10.48550/arxiv.2110.06282
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Rich Get Richer: Disparate Impact of Semi-Supervised Learning

Abstract: Semi-supervised learning (SSL) has demonstrated its potential to improve the model accuracy for a variety of learning tasks when the high-quality supervised data is severely limited. Although it is often established that the average accuracy for the entire population of data is improved, it is unclear how SSL fares with different sub-populations. Understanding the above question has substantial fairness implications when these different sub-populations are defined by the demographic groups we aim to treat fair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…For example, Xu et al [28] studies the setting of adversarial robustness and show that adversarial training introduces unfair outcomes in term of accuracy parity [31]. Zhu et al [33] show that semisupervised settings can introduce unfair outcomes in the resulting accuracy of the learned models. Finally, several authors have also shown that private training can have unintended disparate impacts to the resulting models' outputs [2,10,26,32] and downstream decisions [22,27].…”
Section: Related Workmentioning
confidence: 99%
“…For example, Xu et al [28] studies the setting of adversarial robustness and show that adversarial training introduces unfair outcomes in term of accuracy parity [31]. Zhu et al [33] show that semisupervised settings can introduce unfair outcomes in the resulting accuracy of the learned models. Finally, several authors have also shown that private training can have unintended disparate impacts to the resulting models' outputs [2,10,26,32] and downstream decisions [22,27].…”
Section: Related Workmentioning
confidence: 99%